Perspectives on Momentary Engagement and Learning Situated in Classroom Contexts - Böheim, Ricardo; Symonds, Jennifer (Frontline Learning Research, 2025)
In recent years, there has been a strong call for more fine-grained analyses of student engagement to better capture its nature as a situated, momentary phenomenon. This special issue aims to promote cross-disciplinary discussions about the complex processes involved in students’ momentary engagement and learning situated in classroom contexts. Momentary engagement is conceptualized as students’ involvement with learning activities over short time intervals. We begin by presenting definitional, conceptual, and methodological reflections on the construct of momentary engagement, highlighting how moment-to-moment analyses can deepen our understanding of how engagement unfolds in complex, dynamic learning environments. Next, we discuss the need for a holistic and multidisciplinary perspective to foster an integrative understanding of contexts and conditions under which students engage in academic tasks. Finally, we provide a brief overview of the papers in this special issue, emphasising their diverse methodological approaches to capturing students’ momentary engagement and summarizing their main results that offer practical insights on supporting engagement. Each contribution reflects the efforts of a multidisciplinary team who have studied students’ momentary engagement and learning across various contexts, combining insights and identifying cross-disciplinary synergies in theory and method. The authors integrate perspectives from various fields of research, including motivation, emotion, self-regulation, engagement, social interaction and conceptual change. Their research draws on student samples from the United States, Finland, Ireland, and the United Kingdom.